"Producción y comercialización de plantas clónales de cacao CCN51Theobroma cacao L.) en viveros del cantón Mocache, 2014". - Bueno Mera, Rosa María (2016)
TtHIS RESEARCH WAS CONDUCTEC IN THE MOCACHE CANTÓN, LOS RÍOS PROVINCE, IN NURSERIES MULTIPLICATO+ON OF CLONAL CACAO ccn51 BY COLLECTÍNG PRIMARY DATA USING SURVEYS OF SAMPLE OF 42 MURSYMEN, COMPRISED OF 25 INDEPENDENT AND 17 CERTIFICATES BY AGROCALIDAD.....................................................................